Trifluoromethyl Thianthrenium Triflate: A Readily Available Trifluoromethylating Reagent with Formal CF(3)(+), CF(3)(•), and CF(3)(–) Reactivity - Jia, Hao (J Am Chem Soc, 2021)
[Image: see text] Here we report the synthesis and application of trifluoromethyl thianthrenium triflate (TT-CF(3)(+)OTf(–)) as a novel trifluoromethylating reagent, which is conveniently accessible in a single step from thianthrene and triflic anhydride. We demonstrate the use of TT-CF(3)(+)OTf(–) in electrophilic, radical, and nucleophilic trifluoromethylation reactions.